Health Literacy Practices among Professional Nursing Students in Makassar City - Nur Fadilah; Aulia Insani Latif; Risna Risna; Sakinah Hardiyanti (PT.Mantaya Idea Batara, 2025)
Introduction: Health literacy is a competence that is not only important for patients but also for nursing students. Nursing students will interact with patients with varying health literacy levels during their education and throughout their careers. Despite its importance, research on health literacy among professional nursing students is limited. This study aims to assess the health literacy practices of professional nursing students in Makassar City. This study used a quantitative method with a cross-sectional survey approach. The population in this study consisted of nursing students in the professional nursing stage. The sampling technique is non-probability sampling with consecutive sampling. The respondents involved in this study were 72 nursing students. Data collection was conducted online using a Google Form. The analysis used descriptive statistics, with the results showing frequency distribution, mean, and SD. The study found that among the students, 69.4% were aged 17-25 years, with a mean age of 26.22. The majority were female (75.0%), and from South Sulawesi (80.6%). Related to their education, 73.6% were in the first semester of clinical placement, and have graduated from bachelor of nursing within a year (90.3%). In addition, the average scores for the four aspects of health literacy were: knowledge 14.31 (SD 1.41), communication 34.32 (SD 4.22), shared decision-making 41.11 (SD 5.60), and interpersonal skills 37.49 (SD 4.54). As health literacy is a dynamic skill that needs to be improved through training and experience, nursing education programs must continue to develop students' health literacy competencies from the undergraduate level to the clinical placement stage. Continuous training and periodic assessment of health literacy competencies are recommended to ensure students can apply their knowledge in practice.